(4x-3)(3x-1)-(7x+2)(x+1)=(5x+1)(x-2)-10

Simple and best practice solution for (4x-3)(3x-1)-(7x+2)(x+1)=(5x+1)(x-2)-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x-3)(3x-1)-(7x+2)(x+1)=(5x+1)(x-2)-10 equation:



(4x-3)(3x-1)-(7x+2)(x+1)=(5x+1)(x-2)-10
We move all terms to the left:
(4x-3)(3x-1)-(7x+2)(x+1)-((5x+1)(x-2)-10)=0
We multiply parentheses ..
(+12x^2-4x-9x+3)-(7x+2)(x+1)-((5x+1)(x-2)-10)=0
We calculate terms in parentheses: -((5x+1)(x-2)-10), so:
(5x+1)(x-2)-10
We multiply parentheses ..
(+5x^2-10x+x-2)-10
We get rid of parentheses
5x^2-10x+x-2-10
We add all the numbers together, and all the variables
5x^2-9x-12
Back to the equation:
-(5x^2-9x-12)
We get rid of parentheses
12x^2-5x^2-4x-9x-(7x+2)(x+1)+9x+3+12=0
We multiply parentheses ..
12x^2-5x^2-(+7x^2+7x+2x+2)-4x-9x+9x+3+12=0
We add all the numbers together, and all the variables
7x^2-(+7x^2+7x+2x+2)-4x+15=0
We get rid of parentheses
7x^2-7x^2-7x-2x-4x-2+15=0
We add all the numbers together, and all the variables
-13x+13=0
We move all terms containing x to the left, all other terms to the right
-13x=-13
x=-13/-13
x=1

See similar equations:

| 16^n-7+5=24 | | 2x=3.7 | | x/3.4=2.1 | | 2x−14=10−6x | | 100x89+79=29 | | 14r=9 | | x=14625-1500 | | 39.99+0.45m=44.99+0.40 | | 10x-3x=26 | | 4^2x-3=256^x+1 | | 41=-2a+9 | | 4(x+5)-6(2x+3)=3(x14)-2(5-x)+9 | | 6x+5/3=-13 | | 2(x+5)=5x-14 | | (u−43)÷2u=73 | | 3x-2/6=-10/3 | | -7x*2+7x=0 | | 3/5+2/x=1 | | 8(v-3=16 | | 2x−1=2 | | 9x+4+8x-4+4x+17=180 | | 3x+19=104 | | 20/2x-1=-4 | | 2/5(10x+5)+6=12 | | 22x+6=12 | | 15-x/4=8 | | 80+30+4x+2=180 | | 20+7b=3/4 | | -3x-7+2x=15-5x | | 3960=180n( | | x+88=124 | | 1/2(n+2)+4=3n-5 |

Equations solver categories